2015
DOI: 10.1007/s00702-015-1426-0
|View full text |Cite
|
Sign up to set email alerts
|

Sustained attention in adult ADHD: time-on-task effects of various measures of attention

Abstract: Neuropsychological research on adults with ADHD showed deficits in various aspects of attention. However, the majority of studies failed to explore the change of performance over time, so-called time-on-task effects. As a consequence, little is known about sustained attention performance of adults with ADHD. The aim of the present study was therefore to test the hypothesis of sustained attention deficits of adults with ADHD. Twenty-nine adults with ADHD and 30 healthy individuals were assessed on four 20-min t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
54
2
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 51 publications
6
54
2
4
Order By: Relevance
“…Our failure to identify a consistent time-on-task effect across CPT indices and diagnostic groups may reflect the cognitive complexity of the MOXO-CPT. Previous studies have shown that sustained attention among children and adolescents with ADHD tends to decrease over time with the complexity of task demands [50,51]. For example, Huang-Pollock et al [52] argued that degraded perfor-mance over time in ADHD patients is more evident in tasks that use sensory stimuli (i.e., discriminations of physical characteristics that differ in degree) than in tasks that use cognitive stimuli (i.e., stimuli that differ in type, such as alphanumeric symbols) due to the increased level of effort required in the sensory type.…”
Section: Discussionmentioning
confidence: 99%
“…Our failure to identify a consistent time-on-task effect across CPT indices and diagnostic groups may reflect the cognitive complexity of the MOXO-CPT. Previous studies have shown that sustained attention among children and adolescents with ADHD tends to decrease over time with the complexity of task demands [50,51]. For example, Huang-Pollock et al [52] argued that degraded perfor-mance over time in ADHD patients is more evident in tasks that use sensory stimuli (i.e., discriminations of physical characteristics that differ in degree) than in tasks that use cognitive stimuli (i.e., stimuli that differ in type, such as alphanumeric symbols) due to the increased level of effort required in the sensory type.…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation for the diversity of our findings may be related to the cognitive complexity of the MOXO-CPT paradigm. Previous research has associated the decreased cognitive performance over time in children and adolescents with ADHD with the increased complexity of the task (Tucha et al, 2009(Tucha et al, , 2017Huang-Pollock et al, 2012). For example, in a study with children diagnosed with ADHD, Bioulac et al (2012) found a deterioration of performances over time in a virtual classroom task but not in the CPT.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, diminished sustained attention capacity is hypothesized to underlie various disorders commonly associated with impaired listening, including Auditory Processing Disorder (APD; e.g. Moore et al, 2010Moore et al, , 2013, ADHD (Tucha et al, 2017), autism spectrum disorder (ASD; Corbett and Constantine, 2006) and dementia (Berardi et al, 2005;Calderon et al, 2001). Failure to maintain attention is also observed in hearing impaired individuals (Pichora-Fuller et al, 2016) and as a consequence of healthy ageing (Mishra et al, 2014;Petersen et al, 2017;Schoof and Rosen, 2014).…”
Section: Introductionmentioning
confidence: 99%